2010
DOI: 10.1186/1471-2431-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly high burden of rotavirus gastroenteritis in very young infants

Abstract: Background: The highest incidence of rotavirus gastroenteritis has generally been reported in children 6-24 months of age. Young infants are thought to be partially protected by maternal antibodies acquired transplacentally or via breast milk. The purpose of our study was to assess the age distribution of children with confirmed community-acquired rotavirus gastroenteritis presenting to an urban referral hospital. Methods: Children presenting to The Children's Hospital of Philadelphia with acute gastroenteriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…5 Initial attacks of rotavirus gastroenteritis before the age of 2 y are often debilitating enough to warrant doctor visits or hospitalizations, but deaths are infrequent in the US. [6][7][8] In Philadelphia, rotavirus epidemics have historically commenced in January with the incidence typically peaking in March or April and then quickly subsiding by early June. 6 The surface VP7 and VP4 antigens can be used to classify rotavirus into G and P serotypes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…5 Initial attacks of rotavirus gastroenteritis before the age of 2 y are often debilitating enough to warrant doctor visits or hospitalizations, but deaths are infrequent in the US. [6][7][8] In Philadelphia, rotavirus epidemics have historically commenced in January with the incidence typically peaking in March or April and then quickly subsiding by early June. 6 The surface VP7 and VP4 antigens can be used to classify rotavirus into G and P serotypes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this case it is possible that the first dose of RotaTeq® had not taken, perhaps due to presence of maternally acquired antibodies, and the second dose was effectively the first successful vaccination for this infant. 18,19 Our studies of viral culture showed that G1P [8] double reassortant appears stable in vitro. In the US, sibling transmission of vaccine-derived G1P [8] virus between an immunocompetent vaccinated sibling and a healthy immunocompetent unvaccinated sibling has already been reported.…”
Section: Discussionmentioning
confidence: 98%
“…życia (prawie 80%), a niemal 90% zakażeń RV ma miejsce pomiędzy 3. a 36. mies. życia [4,25,26]. Niemniej jednak do 27% zakażeń występuje przez 6.…”
Section: Epidemiologiaunclassified
“…(ze szczytem w 2. mies. u dzieci w pierwszym półroczu życia) [25]. Większą zapadalność obserwuje się w krajach o wysokim standardzie życia oraz w środowisku miejskim [27].…”
Section: Epidemiologiaunclassified